Effects of individualized word retrieval in kindergarten vocabulary intervention. Issue 3 (2nd July 2016) - Damhuis, Carmen M. P.; Segers, Eliane; Scheltinga, Femke; Verhoeven, Ludo
ABSTRACT: We examined the effects of adaptive word retrieval intervention on a classroom vocabulary program on children's vocabulary acquisition in kindergarten. In the experimental condition, word retrieval was provided in a classroom vocabulary program, combining implicit and explicit vocabulary instructions. Children performed extra word retrieval activities and received semantic feedback for words they did not learn during the classroom vocabulary program. Eighty-seven children were in the experimental condition, and 115 children were in the classroom vocabulary control condition. Results showed the adaptive word retrieval intervention to stimulate higher learning gains than the classroom vocabulary program on the learning of the target words. Children in the experimental condition also showed transfer effects; they described more words on a standardized expressive vocabulary test than children in the control condition. The research findings suggest additional value of word retrieval with feedback for classroom vocabulary learning.